دور الخدمة الاجتماعية في تعزيز اندماج الأطفال المصابين بالتوحد في المجتمع المدرسي (Comprehensive Journal of Science, 2025)
The study aims to examine the role of social work in enhancing the integration of children with autism within the school environment at Najmi Al-Qandouz School for the Rehabilitation and Inclusion of Students with Special Needs. The research adopted a descriptive analytical approach and used data collection tools including questionnaires and interviews with social workers, teachers, and parents. The sample consisted of 40 participants, including children with autism and those working with them.The study concluded that the presence of a social worker contributes to improving the social interaction of children with autism. It also highlighted the importance of cooperation between the family and the school in supporting their inclusion. Furthermore, the study emphasized the need to strengthen the skills of social workers and teachers through continuous training.The findings showed that school activities and programs increase participation and social interaction, despite the existence of some challenges that require additional motivation and support. The study recommended organized programs, training courses, effective communication with families, innovative methods to motivate children, and continuous evaluative follow-up to ensure the sustainability of social inclusion outcomes.